2016
DOI: 10.1038/nn.4264
|View full text |Cite
|
Sign up to set email alerts
|

Hypothalamic control of male aggression-seeking behavior

Abstract: In many vertebrate species, certain individuals will seek out opportunities for aggression, even in the absence of threat provoking cues. While several brain areas have been implicated in generating attack in response to social threat, little is known about the neural mechanisms that promote selfinitiated or "voluntary" aggression seeking when no threat is present. To explore this directly, we utilize an aggression-seeking task wherein male mice can self-initiate aggression trials to gain brief and repeated ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
181
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 221 publications
(188 citation statements)
references
References 48 publications
6
181
0
1
Order By: Relevance
“…Subsequently, Couppis et al (16) and May et al (30) showed that outbred adult male sexually experienced Swiss-Webster resident mice would nose-poke for access to subordinate adult sexually-naïve Swiss-Webster intruders. Most recently, Falkner et al (17) showed that outbred adult male sexually-experienced Swiss Webster resident mice would nose-poke for access to subordinate sexually-naïve inbred Balb/c intruders.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, Couppis et al (16) and May et al (30) showed that outbred adult male sexually experienced Swiss-Webster resident mice would nose-poke for access to subordinate adult sexually-naïve Swiss-Webster intruders. Most recently, Falkner et al (17) showed that outbred adult male sexually-experienced Swiss Webster resident mice would nose-poke for access to subordinate sexually-naïve inbred Balb/c intruders.…”
Section: Discussionmentioning
confidence: 99%
“…There is already some evidence for this. Dominant mice will lever press or nose-poke for the opportunity to attack subordinate intruder mice (1517), as well as form persistent conditioned place preference (CPP) to aggression-paired contexts (18, 19). However, self-administration and CPP are not sufficient to show that a rewarding stimulus is being sought maladaptively, addictively or pathologically (14, 20, 21).…”
Section: Introductionmentioning
confidence: 99%
“…For example, dominant male mice will display conditioned-place preference (CPP) for a distinct context previously paired with a novel submissive opponent (Golden et al 2016a, Golden et al 2016b), a phenotype that stably persists for at least eighteen days (Golden et al 2016a). In addition, socially dominant male mice that repeatedly win aggressive contests will learn to perform an operant task (lever press or nose-poke) that will give them access to attack a subordinate intruder (Fish et al 2002, May and Kennedy 2009, Falkner et al 2016), suggesting that aggression in animals can be positively reinforcing in a manner that is analogous to human instrumental aggression-seeking behavior (Elbert et al 2010, Moran et al 2014). Moreover, up to 20% of mice trained in this type of operant paradigm will exhibit “addiction-like” behavior, expending high levels of effort to gain intruder access, demonstrating robust relapse to aggression-seeking, and displaying resistance to punishment-induced suppression of aggression-seeking behavior (Golden et al 2017).…”
Section: Figurementioning
confidence: 99%
“…Indeed, conspecific aggression can be optogenetically controlled by stimulating or silencing these areas (Falkner and Lin, 2014; Miczek et al, 2015; Unger et al, 2015; Falkner et al, 2016). This neural mechanism is roughly conserved in humans, although the medial prefrontal cortex (mPFC) plays an arguably more prominent role therein (Panksepp, 2011; Yu et al, 2014).…”
Section: Introductionmentioning
confidence: 99%